2019
DOI: 10.1167/iovs.18-25965
|View full text |Cite
|
Sign up to set email alerts
|

IMI – Myopia Genetics Report

Abstract: The knowledge on the genetic background of refractive error and myopia has expanded dramatically in the past few years. This white paper aims to provide a concise summary of current genetic findings and defines the direction where development is needed.We performed an extensive literature search and conducted informal discussions with key stakeholders. Specific topics reviewed included common refractive error, any and high myopia, and myopia related to syndromes.To date, almost 200 genetic loci have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
145
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 153 publications
(181 reference statements)
1
145
2
5
Order By: Relevance
“…Myopia is a complex disease with a multi-factorial etiology. Many experimental and clinical studies have shown that myopia development results from the interplay between genetic and environmental factors [15,16]. Numerous studies demonstrate a higher rate of myopia in children with myopic parents suggesting that genetic factors are clearly involved in myopia development.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is a complex disease with a multi-factorial etiology. Many experimental and clinical studies have shown that myopia development results from the interplay between genetic and environmental factors [15,16]. Numerous studies demonstrate a higher rate of myopia in children with myopic parents suggesting that genetic factors are clearly involved in myopia development.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the general pathomechanism of refractive error development is assumed to be based on a retina-tosclera signalling cascade guided locally by light stimuli in the retina (7). All retinal cell types seem to participate in this retina-speci c signal transduction and derailment of retinal cell physiology and light processing are the key mechanisms (3). However, only recent advances allowed for deeper insight into the genetic background of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize evaluation bias and help with data interpretation, several indicators related to changes in refractive error and myopia progression will also be measured, including AL, corneal curvature, peripheral refraction, parental myopia status, environmental influences, and education insensitivity. In addition, the self-report questionnaire will be used to evaluate compliance and wearing experience [23].…”
Section: Principle Of Outcome Selectionmentioning
confidence: 99%